Investigating the role of urban development in the conventional environmental Kuznets curve: evidence from the globe - Katircioglu, Setareh; Katircioglu, Salih; Kilinc, Ceyhun C. (Springer Heidelberg, 2018)
We investigated the role of urbanization in the conventional environmental Kuznets curve (EKC) of the globe. The overall population and rural population were also considered for control purposes. Based on our findings, we suggest that the conventional EKC of the globe is not an inverted U-shape but becomes downward sloping when urban development is added and inverted U-shapes when the overall population and rural population volumes are added.
Keywords: Environmental Kuznets curve; Energy; Carbon emissions; Urban development